Motivation in Business Organizations - Niraula, Ganesh Prasad (Academic Voices: A Multidisciplinary Journal, 2014)
Motivation is the most important tool for modern organizations. Motivation actually crates drive that leads to the achievement of the individual as well as the organization’s objectives. Now a days many management experts have focused their studies in this field. Moreover not only business organizations, other types of organizations need motivation to obtain their desired goals. It is vital element in the field of education too, as we know very well that a teacher persuade and create drive the students to learn new things and lesson. The present study focuses on concept of motivation, importance of motivation and techniques of motivation at work places. Academic Voices, Vol. 3, No. 1, 2013, Pages 13-18 DOI: http://dx.doi.org/10.3126/av.v3i1.9980